IMPLEMENTASI PEMASARAN BWORK BALI UNTUK MENARIK WISATAWAN DIGITAL NOMAD - Rivi Hatifa, Rheaya; Sudana, I Putu; Kristianto, Yohanes (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 1 (2024): Jurnal IPTA (July 2024), 2024)
Rapid development in technology sparked the emergence of digital nomadism. There are certain facilities to support digital nomads' lifestyle of remote working while traveling, one of which is coworking space. BWork Bali Coworking Space (BWork) is a coworking space located in Canggu, Bali where the area is considered as one of the leading areas for digital nomads around the world. BWork intended to maintain its relationship with digital nomads due to the inconstant trends of digital nomads as its users, as well as to expand its market reach. Therefore, the barriers to marketing activity and marketing communication implementations were analyzed. This research was conducted using qualitative methods and data collection through interviews, documentation, and observation. The study implied that BWork had difficulty reaching digital nomads originating from Asian countries due to language barriers and cultural differences. Also, different views on coworking style among digital nomads could affect their continuity as users and the quality of the internet connection could determine sales, which unstable connection leads to lower sales. The results of the study had shown that BWork prioritized various digital platforms, especially Instagram, to communicate with its members, although not all platforms were managed thoroughly. However, BWork could manage good relationships with digital nomads through events categorized based on digital nomads' needs. Meanwhile, efforts to reach Asian digital nomads have yet to show a significant impact. It is suggested for coworking spaces that target digital nomads as their users should   be able to optimize various digital platforms to reach a wider range of digital nomads who are new to the nomadism lifestyle, have better crowd management and noise control, also form a relationship with digital nomad communities from various countries and actively promote cultures.